DEVELOPMENT OF NIPA (Nypa fruticans) SAP CLOSED COLLECTION VESSEL - James Paul T. Madigal; Bethany Grace S. Calixto Grace S. Calixto; Michael Duldulao; Thomas D. Ubiña; Shirley C. Agrupis (Agro Bali : Agricultural Journal, 2020)
The ultimate goal of the present study was to develop a secure, safe, and hygienic nipa sap collection system for bioethanol production, with the aim of preserving its physico-chemical properties such as physical appearance, pH and sugar brix by reducing the rate of fermentation while attached to the peduncle. The developed collection system was evaluated in terms of the physical and chemical properties of nipa sap collected and ethanol yield in comparison to the traditional and existing collection system used by the nipa community which utilizes bamboo shingle as their collector. Physical appearance of the sap collected using the designed collection system had no foreign materials after harvesting while the traditional collection system had shown traces of insect infestation. The sap that was produced for both of the designed and traditional collection system was milky-white and yellowish-white in color respectively. There was a significant difference in terms of pH concentration of the sap collected using the designed collection system compared to the sap collected using the traditional system overtime. Sugar brix of nipa sap collected using designed collection system is significantly higher than the sap collected using traditional system. A total ethanol yield of 32.25% and 75.54% was obtained for the designed and traditional collection system respectively. Cost Analysis revealed that the designed collection system was found to be cheaper (PhP 11.93) than the traditional collection system (PhP. 20.00). The developed closed collection system can preserved the chemical properties of the nipa sap and could prevent acceleration of fermentation and the deterioration of its potential to yield more ethanol.